Ablation mechanisms of bulk Nb4AlC3 ceramics at 1600–2200 °C in nitrogen plasma flame - Ye Yu; Hao Zhang; Zhen Teng; Yiwang Bao; Man Jiang; Longsheng Chu; Qingguo Feng; Chunfeng Hu (Journal of Materials Research and Technology)
MAX phase ceramics are promising thermal protection materials due to their excellent anti-oxidation and ablation resistance. This paper systematically investigates the ablation behaviors of Nb4AlC3 ceramics in nitrogen plasma flames at 1600–2200 °C. By analyzing changes in ablation rate, microstructure, and elemental composition of the surface and cross-section, the ablation evolution mechanism of Nb4AlC3 ceramics is elucidated. As the ablation temperature increased from 1600 °C to 2200 °C, the linear ablation rate increased from 4.17 to 12.8 μm/s, while the mass ablation rate increased from −4.12 to 22 mg/s. The surface of the ablated Nb4AlC3 underwent decomposition and oxidation reactions, forming oxides (NbO2, Nb2O5, and Al2O3) on the surface. Simultaneously, NbO2 reacted with Al2O3 to form molten AlNbO4, which adhered to the surface and provided protection to the substrate. With increasing ablation temperature, O atoms continuously diffused into the matrix, resulting in a higher O content in the near-subsurface area. These findings indicate that Nb4AlC3 ceramics can withstand plasma flame erosion up to 2200 °C, exhibiting excellent ablation resistance. Therefore, Nb4AlC3 ceramics have significant potential as thermal protection materials.